The Use of SeashellsAsh (Anadara granosa) For Biosorbant of Zn in Water - Ariani, Desi; Siregar, Yusni Ikhwan; Amin, Bintal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted in June 2019 at the Marine Chemistry Laboratory, Department of Marine Sciences, Riau University.The purpose of this study was to determine the ability of ash cockle (Anadara granosa) as biosorbers of zinc (Zn2+).The research was conducted by contacting zinc and blood clam ash with the variation of concentrationof 14 × 103, 20 × 103 and 26 × 103 ppm with a maximum contact time of 24 hours.Zinc analysis performed by using atomic absorption spectroscopy (AAS). The results showed that the ash shells could be used as adsorption material and variations in concentration could affect the absorption of zinc metal. The optimum absorption occurs at a concentration of 14 × 103 ppm with a 24 hour contact time of 99.67%.Key word: Blood Calm Seashell, Adsorbent, Zinc, Atomic Absorption Spectroscopy